Using Microsoft Word, Part One: Lots of Really Useful Stuff. - West, Colin G. (Writers' Journal)
Presents the first article of a two-part series which explores the usefulness of computer operating system, Microsoft Word. Application of the computer operating system; Use of keyboard shortcuts; Provision of techniques on how to use Microsoft Word.